Confiding in others: exploring the experiences of young people who have been in care. (July 2020) - Eldridge, Joshua; John, Mary; Gleeson, Kate
In the general population, confiding is typically associated with increased well-being, reduced distress and strengthened relationships. However, there is a lack of research exploring the role of confiding among young people who have been in the care system. The current study employed Interpretative Phenomenological Analysis (IPA) to guide the analysis of semi-structured interviews with eight young people with a range of care experiences, looking at the topic of confiding in others. Five themes emerged from the data analysis that indicated difficulties with confiding related to: holding unacceptable identities that are difficult to reveal to others; holding anticipations and expectations that confiding leads to harm; experiencing internal conflict between wanting to be open versus wanting to remain closed; and varying opportunities to develop trusted, confiding relationships across different environments within the care system. The findings suggest a need for safe, secure and stable care placements that can support the potential development of trusted confiding relationships wherein young people may be able to develop greater attachment security, and the capacity to build safe, supportive and trusted relationships through their lives. Implications for practice are discussed.